Cardiac resynchronization therapy in chronic heart failure with moderately reduced left ventricular ejection fraction: Lessons from the Multicenter InSync Randomized Clinical Evaluation MIRACLE EF study. (1st January 2016) - Linde, Cecilia; Curtis, Anne B.; Fonarow, Gregg C.; Lee, Kerry; Little, William; Tang, Anthony; Levya, Francisco; Momomura, Shin-ichi; Manrodt, Christopher; Bergemann, Tracy; Cowie, Martin R.
Abstract: Background: The benefits of CRT for symptomatic heart failure (HF) patients with a wide QRS and reduced left ventricular ejection fraction (LVEF ≤ 35%), are well established .Post-hoc subgroup analyses suggest that CRT benefit may extend to patients with LVEF > 35%. Methods: The MIRACLE EF was a prospective, randomized, controlled, double-blinded study to evaluate CRT-P in NYHA II–III HF patients with LBBB and with LVEF of 36%–50% and no previous pacing or ICD. The primary endpoint was a composite of time to first HF event or death. All patients were implanted with a CRT-P and randomized 2:1 to CRT-P ON or CRT-P OFF groups. The minimum follow up time was 24 months. Results: The MIRACLE EF study was stopped for enrollment futility after 13 months and enrolling only 44 patients. The main difficulties in recruiting patients were lack of eligible patients, previous ICD implants, and the reluctance of institutions, patients or physicians to enroll in the study which included a potential 5 year CRT OFF period. Conclusion: Despite a careful design, identification and randomization of eligible patients were challenging and a trial to assess morbidity and mortality trial was not feasible. The MIRACLE EF experience illustrates the difficulties of designing a scientifically robust but feasible study to assess potential new indications for implantable devices. Smaller randomized studies with surrogate endpoints may therefore be more reasonable, although the potential impact of such studies on clinical practice, guidelines, and reimbursement remain to be determined. Highlights: CRT benefits may extend to heart failure patients with less depressed left ventricular function. MIRACLE EF trial aimed to assess CRT benefits in HF patients with LVEF 36–50% and LBBB. The study was stopped early for futility and a trial on morbidity and mortality trial was not feasible. We discuss the difficulties of study design to assess new indications for implantable devices. Smaller RCTs with surrogate endpoints may be more reasonable than morbidity mortality studies.